Health is health is health? Age differences in intraindividual variability and in within-person versus between-person factor structures of self-reported health complaints. - Wolff, Julia Katharina; Brose, Annette; Lövdén, Martin; Tesch-Römer, Clemens; Lindenberger, Ulman; Schmiedek, Florian (Psychology and Aging, 2012)
The variability of health complaints within individuals across time has rarely been studied, and the question whether between- and within-person factor structures of health-related variables are equivalent has not been tested so far. We examined self-reported health complaints in 101 younger (20-31 years) and 103 older adults (65-80 years) over a period of 100 daily assessments. Data were analyzed with confirmatory two-level factor analysis. One-factor structures of health complaints provided an acceptable fit at the between- and average within-person levels in both age groups, supporting the assumption of equivalent average within- and between-person factor structures for health complaints. Age differences in loading patterns indicated that subjective health may be experienced differently by younger and older adults. Small age differences in mean levels of health symptoms were observed. Intraindividual variability in health complaints was reliable. Older adults fluctuated less from day to day than younger adults, presumably reflecting less fluctuation in objective health, differences in response styles, situational influences, or habituation processes. We conclude that future research should consider intraindividual variability as being descriptive of a person's health status, and take possible differences between within- and between-person factor structures of subjective health into account.